Pengembangan Pembelajaran Perakitan PC Berbasis Augmented Reality - Nourazlina, Nourazlina; Pawelloi, A. Irmayani; Yunus, Mughaffir (KOMPUTEK, 2025)
A good understanding of PC components and how to assemble them is a skill that is very much needed in the world of work. However, the PC assembly learning process often faces several obstacles. Such as limited practical tools, limited time, and variations in student understanding. Learning media are needed to help teachers deliver materials and increase student interest in learning. This study aims to develop interactive learning media based on Augmented Reality (AR) to improve student understanding in PC assembly. The research method used is Research quantitative. This learning application was developed using Unity and Blender, which allows students to interact with 3D models in PC assembly simulations. The results of the study show that the use of AR-based learning media can increase the effectiveness and interest of students in understanding PC assembly. The implementation of AR technology in learning allows for clearer visualization and interactive experiences.